The effects of competitive orientation on performance in competition - Ives, J. C.; Neese, K.; Downs, N.; Root, H.; Finnerty, T. (The Sport Journal, 2020)
The competitive environment is reported to influence greater exercise intensity in most persons, thus enhancing practice and training. This effect may be mediated by individual characteristics and the nature of the competitive environment. In particular, persons with non-competitive traits may find live one-on-one physical competition discouraging to full engagement and high effort, but there is little research to support this belief. The purpose of this experiment, thus, was to evaluate the influence of live competition versus no competition (i.e., solo) in persons classified as competitive versus less competitive, or athletes versus non-athlete. After informed consent, 91 subjects were scored on competitive trait using the SOQ tool and grouped into three competitive trait groups (Low, Mid, High). Subjects were also classified as a collegiate varsity athlete or non-varsity athlete. Subjects engaged in maximal vertical jump trials and maximal 40 yard sprint trials under solo conditions and in the presence of another competitor. Maximal single trial performance in the solo condition was compared to the best competition performance and the average competition performance. Repeated measures ANOVA results indicated no significant differences from the solo best trial to the average competition trial in vertical jump height or sprint times. However, the subjects` single best competition sprint trial was significantly faster than the best solo sprint trial, but the best competition vertical jump was not significantly higher than the solo jump. Persons grouped as having a higher competitive trait, and those classified as varsity athletes, had faster sprints and higher jumps, but all groups performed similarly in response to competition. In conclusion, competition produced similar results in all groups, indicating that even less competitive persons and non-varsity athletes respond competitively when in certain circumstances.